IMPLEMENTATION OF KULLIYATUL MU'ALLIMIN AL-ISLAMIYYAH (KMI) CURRICULUM AT PESANTREN PUTRA ULUL ALBAB KOTO BARU DHARMASRAYA - sari, susi puspita (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2023)
The article has the purpose of describing the implementation of the Kulliyatul Mu'allimin al-Islamiyyah (KMI) Curriculum at the Putra Ulul Albab Islamic Boarding School. This research was carried out at the Putren Ulul Albab Islamic boarding school located on Jl. Lintas Sumatera KM 1 Simpang 4 Koto Baru, Dharmasraya regency, West Sumatra. The method used in this study is descriptive quality. The results of this study: 1. Kulliyatul Mu'allimin Al-Islamiyyah (KMI) Curriculum Planning: in general it is the same as the Ministry of Religion planning